Pemanfaatan Limbah Padat Kelapa Sawit untuk Pemurnian Minyak Goreng Bekas - Khairiah, Hanifah; Fatmayati, Fatmayati; Dhora, Anna (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The solid wastes of palm oil are palm shell and boiler ash which can be used as adsorbents. Adsorbent is a solid substance that an adsorption process which is used for the refining process of used cooking oil. Used cooking oil is oil derived from leftover cooking oil which has a higher saturated fatty acid content than new vegetable oil. This study aims to determine the process of making adsorbents, the process of refining used cooking oil, and the effect of adsorbent variations on the purification of used cooking oil. This research was carried out with the adsorption process, adding 15% of the adsorbent variation. The process of making the adsorbent was carried out by dehydration, carbonization at 6000C, and activation with 3% HCl for 24 hours. The results of the optimum adsorbent variation were 100% palm shell adsorbent with the results of analysis on used cooking oil after adsorption, namely: 0.05% water content, 0.58% ALB content, and 1.7 mgO2/100g peroxide number.